Classroom Management: Time-out technique to ensure students behaviour modification: Case of 1st year EFL students at Tlemcen University - Salima, Dali (The International tax journal, 2026)
In didactics, the concept of classroom management refers to the process teachers can use to ensure that their lectures run smoothly without disruptive student behaviour which compromises the delivery of instruction. To do so, different skills and techniques do exist to keep students organized, orderly, focused, attentive, on task, and academically productive during a class. This paper is about the time-out technique, which is now considered a crucial component of many evidence-based behaviours management systems. The main purpose is to theorize that time-out is now used in progressive classrooms to provide an emotional breathing space in a less socially charged area of the room. It also highlights that time-out is a way for students to decompress, reflect on and develop self-awareness, and then return to their seats with improved self-regulation. To do so, a mixed method research design is used based on a questionnaire to teachers and a 1st year EFL Students classroom observation. The main results reveal that in behavioural terms, time-out is a punishment procedure which does not necessarily require removal of the student but rather a continuum of strategies intended to reduce problem behaviour.